Analysis on the Influence of Rural Tourism on Farmers' Income in Western Hunan - Song, Reyu; Li, Zhang (International Journal of Sociologies and Anthropologies Science Reviews, 2024)
Background and Aim: In 2017, the 19th National Congress of the Communist Party of China first proposed the Rural Revitalization Strategy, and two months later, the Rural Work Conference clarified the three goals of implementing this strategy, pointing out that comprehensive rural revitalization should be achieved by 2050. The vitality of rural areas is linked to the vitality of the nation; the strength of the rural areas is tied to the strength of the nation. Implementing the Rural Revitalization Strategy is a significant measure to promote national prosperity and people's happiness, achieve common prosperity, and construct a modern economic system. It points the way to solving the "issues relating to agriculture; rural areas and farmers" and serves as the primary focus in the new era. With China's victory in the fight against poverty in 2021, the focus on the "issues relating to agriculture; rural areas, and farmers" has shifted from poverty alleviation to comprehensive rural revitalization. The purpose of this study is to assess the relevant factors that affect rural tourism and try to improve the income of farmers in western Hunan. Materials and Methods: Based on the panel data of Western Hunan from 2010 to 2020, this paper conducts an empirical study on the influence mechanism of rural tourism development on farmers' income increase in western Hunan. This study uses primarily quantitative analysis methods. It is mainly divided into literature analysis and statistical analysis methods, arranged as follows: Firstly, relevant scholarly research findings and literature sources about the subject matter are retrieved from reputable academic databases such as CNKI (China National Knowledge Infrastructure), Wanfang, and Baidu Academic. The perspectives of domestic and international scholars are elucidated, the existing literature landscape is organized, and the research framework of this article is outlined. Subsequently, the theoretical foundations relevant to the study are identified, and conceptual definitions are formulated. Lastly, the fundamental principles of the theoretical foundations are distilled and enhanced, and a concise summary is provided, culminating in the construction of the theoretical model for this article. Finally, explores the relationship between the rural tourism industry and farmers' income, and takes infrastructure construction, urbanization level, and science and technology level as the variables of mediating effect. Through the statistical analysis software SPSS24 in quantitative research, the reliability and validity of variables were tested, and then statistics and correlation analysis were described, finally, regression analysis was carried out, and data charts were displayed. Results: The results of the model analysis show that the development of rural tourism in western Hunan plays a significant role in promoting the farmers' income. Rural tourism development can not only comprehensively promote the urbanization process, and effectively improve the rural scientific and technological level of Western Hunan, but also contribute to the construction of characteristic ecological civilization and human capital level of western Hunan, and then promote the increase of farmers' income. Conclusion: Therefore, to deepen the promotion effect of rural tourism development on farmers' income, we should first improve the level of rural science and technology and promote the non-agricultural transfer of the rural surplus labor force. Secondly, we should pay attention to the protection of the rural ecological environment and promote sustainable development. At the same time, human capital investment should be strengthened to enhance the quality of farmers themselves. Finally, the government still needs to increase financial support and improve infrastructure construction.